Investigating the Impact of Value Added Tax on Government Size in Iranian Economy Using the Bounds Test - Mohammad Alizadeh; Masoumeh Motallebi (مدلسازی اقتصادسنجی, 2017)
Given the negative impact of oil revenues on government spending and followed by an increase in government size, value-added tax can play an important role in replacing tax revenues with oil revenues. As a new tax that has a wide tax base variation, and also have a positive impact on reducing government size. To examine the impact of VAT on government size, the ratio of total cost has been used to gross domestic product as an indicator of the size of the total government, and the ratio of current expense has been used to gross domestic product as indicator of the size of the current government, and also the ratio of the cost of construction has been used to gross domestic product as the indicator of the size of the state of development. For this purpose, time series statistics model have been used seasonally during the period 2009:1 to 2016:2 by the ARDL model. The results of this study show that there is a positive and significant relationship between Value Added Tax with the size of the total government, and the size of the current government and the size of the state of development. Model estimation results using self-explanatory Autoregressive Distributed Lag (ARDL) and Bound Testing approach show that dynamic model moves towards a long-term pattern in all three models.